2013
DOI: 10.1063/1.4802874
|View full text |Cite
|
Sign up to set email alerts
|

A theory for structural phase transitions in BaTiO3 single crystal and PbZrO3 -xPbTiO3 solid solution

Abstract: A phenomenological theory has been proposed for the diffusionless structuralphase transitions in BaTiO3single crystal and PbZrO3 -xPbTiO3 solid solution here. It has been found that for BaTiO3single crystal, both the phase transitionsand the crystal structurescan be predicted with the crystalline anisotropy constants and strain constants that depend on the temperature. For PbZrO3 -xPbTiO3 solution, the morphotropic phase boundaries arise from the strong dependence of the crystalline anisotropy constants on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
(44 reference statements)
2
11
0
1
Order By: Relevance
“…The investigations of BaTiO 3 and PZN-PT single crystals have shown that the model is in good agreement with experimental data, and effective for both polarization rotation and phase transitions in the crystals. [19][20][21][22] These results also suggested that the electrocrystalline anisotropy determines not only the polarization rotation but also the crystal structure of crystal, and clearly indicates its physical significance. However, there is another anisotropy associated with an applied stress.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…The investigations of BaTiO 3 and PZN-PT single crystals have shown that the model is in good agreement with experimental data, and effective for both polarization rotation and phase transitions in the crystals. [19][20][21][22] These results also suggested that the electrocrystalline anisotropy determines not only the polarization rotation but also the crystal structure of crystal, and clearly indicates its physical significance. However, there is another anisotropy associated with an applied stress.…”
Section: Introductionmentioning
confidence: 59%
“…In our previous work, a phenomenological theory has been proposed for understanding polarization rotation in ferroelectric crystals. 19,20 In this model, the electrocrystalline anisotropy has been introduced without considering the piezoelectric effect. The investigations of BaTiO 3 and PZN-PT single crystals have shown that the model is in good agreement with experimental data, and effective for both polarization rotation and phase transitions in the crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental observations have demonstrated that the sequence of decreasing temperature phase transitions is more complex and as follows: cubic‐tetragonal‐orthorhombic‐rhombohedral. For these ferroelectric phases, the spontaneous polar directions are also accordingly changing from the <100> axis to the <110> axis, and then to the <111> axis as the temperature decreases …”
Section: Introductionmentioning
confidence: 99%
“…Recently, the replacement of Ca for Ba in BTO has attracted many attentions due to its interesting properties, especially its piezoelectric property. The first report on Ba 1-x Ca x TiO 3 (BCT) composite [3,4] showed that the structure phase transition temperature T T-O (tetragonal to orthorhombic) of BCT samples much reduces in dependence of Ca concentration while the Curie temperature T c remains unchanged at 130 0 C. The dependence of T c and T T-O on Ca concentration is quite different in case of Sr substitution for Ba in BTO. In the fact that, the decreasing in T c and T T-O in case of the Sr substitution was attributed to the ionic radius effect, the ionic radius of Sr 2+ is smaller than that of Ba 2+ [1,2,5].…”
Section: Introductionmentioning
confidence: 99%